2014
DOI: 10.1111/dmcn.12588
|View full text |Cite
|
Sign up to set email alerts
|

Are children with acute arterial ischaemic stroke eligible for hyperacute thrombolysis? A retrospective audit from a tertiary UK centre

Abstract: Aim The aim of this study was to evaluate the number of children with acute arterial ischaemic stroke (AIS) who would have been eligible for hyperacute thrombolysis in the authors' unit (Great Ormond Street Hospital, London, UK) and to identify barriers to this treatment. Method We compared the characteristics of children with a diagnosis of acute AIS, identified from neuroimaging databases, seen at our centre between January 2006 and December 2011. The criteria for hyperacute thrombolysis were predefined by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Although the benefit of thrombolytic therapy in PAIS has yet to be demonstrated in prospective clinical trials, retrospective studies show that at least a subset of children with AIS may potentially benefit from it. 21,22 Several tertiary pediatric centers have developed standardized systematic strategies to diagnose and treat PAIS, for participation in the ongoing Thrombolysis in Pediatric Stroke trial. 21,22 Ischemic penumbra can be depicted as a mismatch between reduced perfusion and normal diffusion by combining PWI and DWI/DTI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the benefit of thrombolytic therapy in PAIS has yet to be demonstrated in prospective clinical trials, retrospective studies show that at least a subset of children with AIS may potentially benefit from it. 21,22 Several tertiary pediatric centers have developed standardized systematic strategies to diagnose and treat PAIS, for participation in the ongoing Thrombolysis in Pediatric Stroke trial. 21,22 Ischemic penumbra can be depicted as a mismatch between reduced perfusion and normal diffusion by combining PWI and DWI/DTI.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Several tertiary pediatric centers have developed standardized systematic strategies to diagnose and treat PAIS, for participation in the ongoing Thrombolysis in Pediatric Stroke trial. 21,22 Ischemic penumbra can be depicted as a mismatch between reduced perfusion and normal diffusion by combining PWI and DWI/DTI. 23 In children, however, the routine application of PWI outside research protocols and tertiary care centers is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…In a large retrospective cohort analysis, Mallick et al reviewed 107 pediatric patients and found that only three patients would have been eligible for hyperacute thrombolysis with IV tPA. 56 This study and the slow recruitment of patients to the TIPS (Thrombolysis In Pediatric Stroke) trial demonstrates the degree of difficulty in achieving timely access to thrombolytic therapy in the pediatric patient group. Since 2015 the established benefit of MT in adults has shown tremendous improvement in neurological function in recanalized patients in real-world application of randomized trial results.…”
Section: Pediatric Patients With Elvomentioning
confidence: 92%
“…Marecos et al . [ 13 ] subsequently reported a retrospective 5-year audit on the eligibility for thrombolytic therapy in a tertiary center in the UK. The aim was to define local criteria for children with hyperacute ischemic strokes who might benefit from thrombolysis, to examine how many would have met these criteria, and to describe the barriers to hyperacute treatment in childhood ischemic strokes.…”
Section: Can Ischemic Strokes In Children Be Thrombolysed?mentioning
confidence: 99%